Isomap nonlinear dimensionality reduction and bimodality of Asian monsoon convection. Issue 8 (29th April 2013) - Hannachi, A.; Turner, A.G.
Abstract : [1] It is known that the empirical orthogonal function method is unable to detect possible nonlinear structure in climate data. Here, isometric feature mapping (Isomap), as a tool for nonlinear dimensionality reduction, is applied to 1958–2001 ERA‐40 sea‐level pressure anomalies to study nonlinearity of the Asian summer monsoon intraseasonal variability. Using the leading two Isomap time series, the probability density function is shown to be bimodal. A two‐dimensional bivariate Gaussian mixture model is then applied to identify the monsoon phases, the obtained regimes representing enhanced and suppressed phases, respectively. The relationship with the large‐scale seasonal mean monsoon indicates that the frequency of monsoon regime occurrence is significantly perturbed in agreement with conceptual ideas, with preference for enhanced convection on intraseasonal time scales during large‐scale strong monsoons. Trend analysis suggests a shift in concentration of monsoon convection, with less emphasis on South Asia and more on the East China Sea. Key Points: Paper demonstrates bimodality in monsoon intraseasonal variability Methodology combines both the nonlinearity and high dimensionality of monsoon Suggests enhanced predictability of active/break monsoon phases variability